Disrupted dispersal and its genetic consequences: Comparing protected and threatened baboon populations (Papio papio) in West Africa - Silva, Maria Joana Ferreira da (2018)
Dispersal is a demographic process that can potentially counterbalance the negative impacts of anthropogenic habitat fragmentation. However, mechanisms of dispersal may become modified in populations living in human-dominated habitats. Here, we investigated dispersal in Guinea baboons (Papio papio) in areas with contrasting levels of anthropogenic fragmentation, as a case study. Using molecular data, we compared the direction and extent of sex-biased gene flow in two baboon populations: from Guinea-Bissau (GB, fragmented distribution, human-dominated habitat) and Senegal (SEN, continuous distribution, protected area). Individual-based Bayesian clustering, spatial autocorrelation, assignment tests and migrant identification suggested female-mediated gene flow at a large spatial scale for GB with evidence of contact between genetically differentiated males at one locality, which could be interpreted as male-mediated gene flow in southern GB. Gene flow was also found to be female-biased in SEN for a smaller scale. However, in the southwest coastal part of GB, at the same geographic scale as SEN, no sex-biased dispersal was detected and a modest or recent restriction in GB female dispersal seems to have occurred. This population-specific variation in dispersal is attributed to behavioural responses to human activity in GB. Our study highlights the importance of considering the genetic consequences of disrupted dispersal patterns as an additional impact of anthropogenic habitat fragmentation and is potentially relevant to the conservation of many species inhabiting human-dominated environments.